Changes in the aerobic saprophytic microbial flora during biltong production with special reference to the micrococcaceae - Taylor, M B (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1976)
Ninety-four presumptive Micrococcus and Staphylococcus strains isolated from both commercial beef biltong and game biltong, were identified using a scheme based on the system used by Baird-Parker. The changes occurring in both the aerobic, saprophytic microbial flora and the environmental factors, during conversion of beef to biltong, were examined. The predominantly Gram-negative, halo-sensitive flora initially present on the meat, was replaced by Gram-positive, halo-tolerant staphylococci and micrococci, which form the dominant component of the microflora of the final product. This replacement was attributed to changing environmental factors, principally to the increasing sodium chloride concentration and associated decline in water activity. The presence of the antifungal antibiotic, pimaricin, during processing did not influence the bacterial flora of the product. However, the addition of potassium sorbate altered the microbial profile of the product significantly. The presence of these two preservatives, at the concentrations used, could not be detected organoleptically. The importance of the saprophytic microflora of the product ln relation to the environmental factors during processing, is also discussed.
Keywords: Micrococcaceae; Saprophytism